DIRECTIVE SPEECH ACTS OF 'BASO PALEMBANG SARI-SARI' : REVIEW OF LANGUAGE POLITENESS - Atika, Ummi Nur; Mayrita, Hastari (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
This study aims to describe direktif speech acts used in everyday Palembang conversations and to explore the politeness functions used in everyday Palembang conversations. This study uses a qualitative method with a case study approach. The data source for this research was taken from the conversations of Palembang residents about how to use 'Baso Palembang Sari-Sari' or what is known as the everyday use of Palembang language. While the community is speaking, the researcher observes the ongoing conversation, then the researcher records, encodes, and transcribes the speech of the community to determine which utterances are classified as directive speech acts. The data was taken from community chats using the Baso Palembang Sari-Sari language. The data analysis technique used in this study uses thematic techniques and content analysis. The results of this study indicate that there are six types of directive speech acts in the speeches of 'Baso Palembang Sari-Sari', namely invitations, requests, orders, advice, criticisms and prohibitions. As well as finding 6 functions of politeness in Palembang language in speaking.